2004
DOI: 10.1016/j.ijmedinf.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing medical residents’ usage and perceived needs for personal digital assistants

Abstract: ] on the use of PDAs at the point of care found that hardware constraints, such as memory capability limited their usefulness, however, they were used frequently for accessing medical references and drug information [The Constellation Project: experience and evaluation of personal digital assistants in the clinical environment, in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
78
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 12 publications
2
78
1
2
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14] Acting as important benchmarks, these studies offered the first glimpses into the adoption of EHR and PDAs in specific settings or by specific groups of physicians. The majority of studies examining PDA use by primary care physicians, for instance, focused on the academic setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14] Acting as important benchmarks, these studies offered the first glimpses into the adoption of EHR and PDAs in specific settings or by specific groups of physicians. The majority of studies examining PDA use by primary care physicians, for instance, focused on the academic setting.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies examining PDA use by primary care physicians, for instance, focused on the academic setting. [4][5][6][7][8][9] Consequently, the results of these studies might not be applicable to nonacademic and community settings. Similarly, EHR use has been studied in populations of academic or researchoriented primary care physicians.…”
Section: Introductionmentioning
confidence: 99%
“…In October 2010, another study showed that 85% of all American adults, 96% of those were aged 18-29 years, and 90% of those aged 30-49 years own a cell phone (Smith 2010a). Work has previously been done looking at the trends of handheld computing and mobile device use in graduate medical education (Barrett et al 2004;Sutton et al 2004;Mattana et al 2005;Khan et al 2007;Morris et al 2007), with undergraduate medical students (Grasso et al 2005;Kho et al 2006;Kennedy et al 2008;Norman et al 2008;Chatterley & Chojecki 2010;Ferenchick et al 2010;Lasserre et al 2010), and the health care setting (Garritty & El Emam 2006;Ranson et al 2007;Trelease 2008;Evans & Stacey 2009). Looking specifically at medical students, Grasso et al (2005) surveyed preclinical and clinical medical students and found that the clinical students used drug references and medical calculators on their handheld device.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in the literature have investigated the use of mobile devices in both undergraduate and graduate medical education. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] In a US study of cell phone use in medical students, 94 % of third-year medical students at a Midwestern University …”
mentioning
confidence: 99%